Koszty zasobów ludzkich w controllingu przedsiębiorstwa - Kaczyńska, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The subject of this paper are the human resource costs and their place in controlling, particularly in personal controlling. Increasement of the meaning of personal function causes requirement of analysis of human resources from financial part, i.e. the costs and the profits. Operations connected with planning and controlling those categories should be realized within the confines of personal controlling. And so the paper presents the essence and the range of human resource costs and it presents the basics of the estimation of these cost, as well as the instruments, including basic indexes, witch are applied in the area of the work costs. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 88-94